The Role of the Regional Supervisory Board in Supervising the Notary Code of Ethics in Central Java Province - Hartono, Vania Cahya; Sudarwanto, Albertus Sentot; Mulyanto, Mulyanto (Jurnal Daulat Hukum, 2025)
This study aims to analyze the implementation of supervision by the Notary Supervisory Board (MPW) of Central Java Province regarding the implementation of the notary professional code of ethics, as well as the obstacles and solutions encountered. The research method used is normative legal research with a statute approach and a case approach. Legal sources include laws and regulations, notary codes of ethics, ministerial regulations, and secondary literature in the form of books, journals, and scientific articles. The results of the study indicate that normatively, the regulations regarding notary supervision are adequate as stipulated in Law No. 30 of 2004 in conjunction with Law No. 2 of 2014 concerning the Position of Notary, the Regulation of the Minister of Law and Human Rights, and the Notary Code of Ethics. However, in practice, obstacles are still found, such as budget limitations, low notary compliance with summons, weak deterrent effects of sanctions, and overlapping authority with the Notary Honorary Council. Nevertheless, the MPW continues to strive to carry out supervision through coaching, routine inspections, and recommendations for sanctions. For more effective oversight, data synchronization, improved coordination between levels of the assembly, stricter enforcement of sanctions, and strengthening of preventive functions through professional ethics education and outreach are required. Thus, the MPW is expected to maintain notary integrity while providing better legal protection for the public.